Case Report: Cancer spectrum and genetic characteristics of a de novo germline POLD1 p.L606M variant-induced polyposis syndrome - Zhang, Ying; Wang, Xiaolu; Zhu, Yuning; Liang, Chong; Zhao, Lijun; Meng, Qi; Yin, Jiani C.; Shi, Yuqian; Wang, Fufeng; Qin, Feng; Xuan, Ji (Frontiers in Oncology, 2023)
Germline variations in the DNA polymerase genes, POLE and POLD1, can lead to a hereditary cancer syndrome that is characterized by frequent gastrointestinal polyposis and multiple primary malignant tumors. However, due to its rare occurrence, this disorder has not been extensively studied.In this report, we present the case of a 22-year-old female patient who had been diagnosed with gastrointestinal polyposis, breast fibroadenoma, multiple primary colorectal cancers, and glioblastoma (grade IV) within a span of four years. Next-generation sequencing analysis revealed a germline variant in POLD1 (c.1816C>A; p.L606M). In silico analysis using protein functional predicting software, including SIFT, Polyphen, GERP++, and CADD, further confirmed the pathogenicity of POLD1 p.L606M (classified as ACMG grade Class 4). In line with polymerase deficiency, both rectal cancer and glioblastoma tissues exhibited a high tumor mutation burden, with 16.9 muts/Mb and 347.1 muts/Mb, respectively. Interestingly, the patient has no family history of cancer, and gene examination of both parents confirms that this is a de novo germline variant.Therefore, molecular screening for POLD1 may be necessary for patients with such a cancer spectrum, regardless of their family history.